2013
DOI: 10.1016/j.bbr.2012.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Human handedness: An inherited evolutionary trait

Abstract: Our objective was to demonstrate that human right-handedness, is not species specific, precipitated from language areas in the brain, but rather is context specific and inherited from a behavior common to both humans and great apes. In general, previous methods of assessing human handedness have neglected to consider the context of action or employed methods suitable for direct comparison across species. We employed a bottom-up, context-sensitive method to quantitatively assess manual actions in right-handed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 91 publications
5
50
0
3
Order By: Relevance
“…For gorillas, we employed two digital video cameras (Panasonic NVGS11B), one with a close view on the focal subject and one with a wider view of the surrounding social environment. Video footage was synchronized using a flash bulb (see Forrester, 2008;Forrester et al, 2011Forrester et al, , 2012Forrester et al, , 2013. Video streams were later compressed into a single file of 15 frames/s and composed by a top/bottom format for subsequent coding (i.e., focal view in the top and wide view in the bottom).…”
Section: Methodsmentioning
confidence: 99%
“…For gorillas, we employed two digital video cameras (Panasonic NVGS11B), one with a close view on the focal subject and one with a wider view of the surrounding social environment. Video footage was synchronized using a flash bulb (see Forrester, 2008;Forrester et al, 2011Forrester et al, , 2012Forrester et al, , 2013. Video streams were later compressed into a single file of 15 frames/s and composed by a top/bottom format for subsequent coding (i.e., focal view in the top and wide view in the bottom).…”
Section: Methodsmentioning
confidence: 99%
“…The authors noted that traditional studies of handedness were narrowly defined and did not represent the naturalistic actions of daily life. A recent study of children also found that hand dominance varied across targets, even in those who are otherwise considered right-hand dominant by parent report [56]. The authors demonstrated that while typically developing right-handed boys (aged 4-5 years) expressed a significant right hand dominance for object manipulation, no hand preference was found for hand actions directed toward social partners and the self.…”
Section: Introductionmentioning
confidence: 93%
“…In studies of motor lateralization, social context has been suggested to incorporate different patterns of hemispheric specialization in the performance of the action as compared with non-social context (Forrester et al, 2014b). Generally, actions directed to social partners and the self tend to increase the left hand use indicating greater involvement of right hemisphere (Forrester et al 2013;Rogers and Kaplan, 1995). Based on this concept, we suggest that social context can favour or at least modify the expression of lateralization of trunk use in elephants as compared with non-social context.…”
Section: Animal Behaviourmentioning
confidence: 99%